2021
DOI: 10.1002/aoc.6204
|View full text |Cite
|
Sign up to set email alerts
|

Diverse coordination geometry of cobalt (II), zinc (II), and cadmium (II) complexes comprising N,N‐bis(1H‐pyrazol‐1‐yl)methyl)amines derivatives: Synthesis, structures, and ring opening polymerization of rac‐lactide

Abstract: A series of six new complexes of Co (II), Zn (II), and Cd (II) supported by bis (1H-pyrazol-1-yl)methyl)amine derivatives (N,N-bis((1H-pyrazol-1-yl)methyl)-1-phenylethanamine (L A ), N,N-bis((1H-pyrazol-1-yl)methyl)-1-(furan-2-yl) methanamine (L B ), and N,N-bis((1H-pyrazol-1-yl)methyl)-4-isopropylaniline (L C ) synthesized. The direct chelation of the ligands (L n = L A − L C ) with ZnCl 2 , CoCl 2 .6H 2 O, and CdBr 2 Á4H 2 O produced [L n MX 2 ] (L n = L A − L C ; M = Zn, Co; X = Cl; M = Cd, X = Br) and [L C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 85 publications
1
3
0
Order By: Relevance
“…However, further increase in the [ rac -LA] 0 /[catalyst] ratio up to 700:1 resulted in only 31% conversion under identical experimental protocols, and a decrease in the molecular weight of resultant PLA was also observed with this decrease in conversion (Figure ). Depending on the metal center variation, [L TH ZnCl 2 ]/LiO i Pr resulted in a high heterotactic enchainment ( P r = 0.74 at 0 °C) compared to its Cd­(II) and Pd­(II) complexes, consistent with the findings of previous studies. , Decrease in polymerization temperature did not show any significant enhancement of the heterotactic bias, particularly for the Cd­(II)-based initiator. The geometry of the M­(II) complex might have steered the hetereotacticity of PLA in the studied complexes.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, further increase in the [ rac -LA] 0 /[catalyst] ratio up to 700:1 resulted in only 31% conversion under identical experimental protocols, and a decrease in the molecular weight of resultant PLA was also observed with this decrease in conversion (Figure ). Depending on the metal center variation, [L TH ZnCl 2 ]/LiO i Pr resulted in a high heterotactic enchainment ( P r = 0.74 at 0 °C) compared to its Cd­(II) and Pd­(II) complexes, consistent with the findings of previous studies. , Decrease in polymerization temperature did not show any significant enhancement of the heterotactic bias, particularly for the Cd­(II)-based initiator. The geometry of the M­(II) complex might have steered the hetereotacticity of PLA in the studied complexes.…”
Section: Resultssupporting
confidence: 89%
“…Depending on the metal center variation, [L TH ZnCl 2 ]/LiO i Pr resulted in a high heterotactic enchainment ( P r = 0.74 at 0 °C) 61 compared to its Cd(II) and Pd(II) complexes, consistent with the findings of previous studies. 62 , 63 Decrease in polymerization temperature did not show any significant enhancement of the heterotactic bias, particularly for the Cd(II)-based initiator. The geometry of the M(II) complex might have steered the hetereotacticity of PLA in the studied complexes.…”
Section: Resultsmentioning
confidence: 93%
“…Almost all the transition metals from group 8 to group 10 in the periodic table can be coordinated by the N-heterocyclic ligands. 1–4 Thus, transition metal complexes based on various types of N-heterocyclic ligands have been synthesized and employed in many areas, especially as efficient catalysts in diverse organic reactions, including hydrogenation, 5 oxidation, 6,7 polymerization, 8,9 cross-coupling, 10–16 amidation, 17,18 and reductive amination. 19–21 On the other hand, the prevalence of the N-heterocyclic motif in biologically active molecules has encouraged systematic explorations of such types of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) and coordination polymers (CPs) are very attractive because of their designability and/or tunability in both crystalline structure and functionality, which offer an opportunity for developing advanced functional materials. , Structural transformations, especially single-crystal to single-crystal (SCSC) transformations, in these polymeric materials are attractive because they usually occur cooperatively with interesting phenomena that might promote and/or introduce exotic functionalities into the materials. These particular properties could be triggered by various stimulators such as light, solvent, guest sorption–desorption, and even chemical reactions. The SCSC transformation in coordination compounds, in some cases, causes a conversion of the metal coordination geometry that leads to a change in material properties such as optical properties, as well as catalytic activity. Along with the exponential increase in the number of reported MOFs, various synthetic methods have been intensely explored in order to reduce the consumption of time and energy as well as minimize chemical waste. , Among the rapid and green synthetic routes to porous MOFs, the microwave-assisted technique has become one of the promising alternative ways that can facilitate the repeatable and controllable productions of these functional materials within a few minutes. On the other hand, among the numbers of MOFs that exhibit semiconduction, the well-known Zn-MOF [Zn 4 O­(BDC) 6 ] or MOF-5, with a band gap energy of 3.4–4.0 eV, showed photocatalytic activity upon phenol degradation . Apart from ZnO semiconductors as photocatalysts, the potential application of Zn-MOFs in photocatalysis has become more attractive. , In addition, SCSC transformation studies involving both ligand substitution and time have rarely been reported and may reveal a greater understanding of the kinetics of the transformation .…”
Section: Introductionmentioning
confidence: 99%